Transforming text to music using artificial intelligence improves the frontal lobe function of normal older adults - Satoh, Masayuki; Inoue, Jun; Ogawa, Jun‐ichi; Tabei, Ken‐ichi; Kamikawa, Chiaki; Abe, Makiko; Yoshizawa, Ayaka; Kitagawa, Gyo; Ota, Yosinori (Brain and behavior, 2024)
Introduction Recent advances in artificial intelligence (AI) have been substantial. We investigated the effectiveness of an online meeting in which normal older adults (otokai) used a music‐generative AI that transforms text to music (Music Trinity Generative Algorithm‐Human Refined [MusicTGA‐HR]). Methods One hundred eighteen community‐dwelling, cognitively normal older adults were recruited through the internet (64 men, 54 women; mean age: 69.4 ± 4.4 years). Using MusicTGA‐HR, the participants chose music that they thought was the most suitable to a given theme. We established 11 classes of 7–10 members and one instructor each. Each class held an online meeting once a week, and each participant presented the music they chose. The other participants and the instructor then commented on the music. Neuropsychological assessments were performed before and after the intervention for 6 months, and the results before and after the intervention were statistically analyzed. Results The category and letter word fluencies (WFs) were significantly improved (category WF: p = .003; letter WF: p = .036), and the time of the Trail‐Making Test‐B was also significantly shortened (p = .039). The Brain Assessment, an online cognitive test we developed, showed significant improvement in the memory of numbers (p < .001). Conclusion The online meeting of the otokai, which used music‐generative AI, improved the frontal lobe function and memory of independent normal older adults. We investigated the effectiveness of an online meeting in which normal older adults (otokai) used a music‐generative artificial intelligence (AI) that transforms text to music (Music Trinity Generative Algorithm‐Human Refined [MusicTGA‐HR]). Using MusicTGA‐HR, the participants chose music that they thought was the most suitable to a given theme. Each class held an online meeting once a week for 6 months, and each participant presented the music they selected. As a result, the frontal lobe function and memory were improved.